Iron overload promotes myeloid differentiation of normal hematopoietic stem cells and educates macrophage mediated immunosuppression in acute myeloid leukemia - Feifei Yang; Shulin Luo; Dan Yang; Xiaoxi Cui; Dongyue Zhang; Hao Wang; Yifei Li; Wanzhen Xie; Lina Wang; Lina Wang; Xiuqun Zhang; Guoguang Zheng; et al. (Frontiers in Immunology)
BackgroundThe hematopoietic ecosystem comprises both cellular components such as hematopoietic stem cells (HSCs) and immune cells as well as non-cellular components including iron. Systemic iron overload, which leads to serious complications and affects both patients’ quality of life and overall survival, is a common clinical challenge in patients with acute myeloid leukemia (AML). We previously elucidated the direct effects of iron overload on AML cells. It’s worth noting that iron overload remodels the hematopoietic ecosystem. However, whether and how remodeled leukemic microenvironment with overloaded iron regulates normal HSCs and immune cells, especially leukemia-associated macrophages (LAMs), in AML have not been elucidated.MethodsThe MLL-AF9-induced AML (MA9) cells were originated from c-kit+ BM cells enriched from C57BL/6J mice that infected with MSCV-MLL-AF9-GFP retrovirus. The MA9 AML mouse model was established by transplantation of MA9 cells into C57BL/6 mice. MA9 mice were i.p. administered with iron dextran every other day for a total of 6 times to established the iron overload MLL-AF9-induced AML mouse model (MA9/FE). HSC maintenance and differentiation was assessed by flow cytometry, cell proliferation, cell apoptosis, colony forming and competitive transplantation assays. LAM activation and function was analyzed by RNA-sequencing, flow cytometry and coculture assay. Intravenous clodronate liposome administration was employed to reduce LAMs in AML.ResultsIron overload skewed myeloid differentiation of normal HSCs. Furthermore, iron overload affected LAMs in the AML microenvironment by promoting LAM polarization toward an M2 phenotype. Functionally, iron overload decreased the phagocytic function of LAMs against leukemia cells and inhibited LAM-induced T cell activation by acquiring a tolerogenic phenotype with aberrant immune checkpoints. Moreover, depletion of LAMs attenuated iron overload caused acceleration of AML progression.ConclusionsCollectively, this study reveals the significance of iron overload in remodeling hematopoietic ecosystem and affecting HSC and LAM function in AML, providing new insights into the multifaceted role of iron overload in leukemia.